The Future Internet Alternative Visions - Winter, Jenifer; Ono, Ryota (Public Administration and Information Technology, 2015)
The internet's global expansion has been the subject of much academic research and policy discourse in recent years. Due to the sociotechnical complexity of the Internet, policymakers, businesspeople, and academics worldwide have struggled to keep abreast of developments. Readers seeking to gain a handle on the field will find this book rich in scholarly foundations combined with cutting-edge discussion of emerging ICTs and services and the complex societal contexts in which they are embedded. To explore possibilities to the fullest extent, a sociotechnical systems approach is employed, focusing on the interplay of technical, social, cultural, political, and economic dynamics to explore alternative futures (ones that are not part of the dominant discourse about the internet). The shared perspectives are not well addressed elsewhere in current discussions. Awareness of these dynamics, and the fluidity of the future, is important, as humankind moves forward into the uncertain future. This approach is intended to stimulate dialogue between academics and practitioners on a topic that will affect most aspects of human life in the near-term future.